Forensic markers for revealing bloody fingerprints: a brief review (Research, Society and Development, 2022)
The development of luminescent materials has been extremely relevant in the field of forensic science, due to the significant contributions to improving latent fingerprint development, image quality, and the detection of numerous traces at crime scenes. In this sense, this article aims to review the methods used and the materials with promising luminescent properties for application in forensic markers to reveal fingerprints with blood on different surfaces. In addition, we will analyze the development of new technologies and the optimization of existing methods to find better solutions to the issues that criminal experts face during a forensic investigation, such as improving factors such as toxicity, sensitivity, surface, and material efficiency. and the development methods, using approaches based on fluorescent materials such as nanoparticles doped with rare earth, 1,8-diazafluoren-9-one, acid dyes, and ninhydrin. Therefore, it was found that more research is needed to better understand the reaction mechanism involved in these materials, as well as the development of new efficient materials, with low toxicity and more sensitivity for processing latent fingerprints on different surfaces.